Possíveis contribuições de atividades investigativas para o desenvolvimento de capacidades do pensamento crítico - Souza, Renata Suellen Bomfim (2019)
An investigative activity (AI) is a problem-solving approach, allowing students to engage in knowledge construction. Several authors defend the use of AI for the development of the critical formation of individuals, therefore, to develop critical thinking. However, how do you ensure that an investigative approach will meet these objectives? It is necessary to consider factors related to AI that influence and potentiate its approach and that refer to the construction of knowledge combined with the improvement of attitudes and values, essential in the critical formation of students, driven by the mobilization of aspects of critical thinking in scientific education. Therefore, the main objective of this research was to investigate the possible capacities of Critical Thinking. Research Activities can contribute to the construction of knowledge, attitudes and values in a research perspective approached in a contextualized approach, in the form of a thematic workshop. Based on the theoretical foundations of AI and Critical Thinking Theory (CP) in teaching, we propose in this dissertation an investigation about the potential capacities of the CP mobilized in students who undergo AI approaches. As a way to relate AI and PC in these approaches, in the form of a first article, we look for in official documents that govern the teaching of Chemistry in Brazil about competences and abilities to establish relations with PC capabilities potentially mobilized in students. Thus, the present research initially presents an alignment between PC skills with skills and abilities in official documents, such as Curricular Parameters, since, the official Brazilian documents preach the promotion of competences in the scope of Science teaching as a means of training the critical student After alignment, in the form of a second article, we discuss the data collected through the application of an AI, in order to verify if there was mobilization of PC capabilities in classroom practice. The data collection took place in four different classes and will be supported by the theoretical framework of Content Analysis (Bardin), to investigate the students' ideas and to verify if there was the mobilization of the PC capabilities proposed by AI. In the documentary analysis carried out initially, it can be seen that the competences proposed by the PCN + mainly propitiate the mobilization of elementary capacities of the CP, indicating that the Brazilian education is focused on the development of basic capacities in the critical formation of individuals, according to the reasoning of the adopted reference . Already in the analysis of the data collected in the AI, it was verified the mobilization of basic competences of the investigation process, directing, therefore, the mobilization of PC capabilities in elementary areas such as Elementary Clarification, also providing a reflection on the actions of PIBID.